Virtually sacred: myth and meaning in World of Warcraft and Second Life - Geraci, Robert M. (Oxford University Press, 2014)
Video games and virtual worlds can rearrange or replace religious practice as designers and users collaborate in the production of a new spiritual marketplace. Using 'World of Warcraft' and 'Second Life' as case studies, this book shows that many residents now use virtual worlds to reimagine their traditions and work to restore them to 'authentic' sanctity or replace religious institutions with virtual world communities that provide meaning and purpose to human life.